MODEL PENGEMBANGAN DESA CERDAS (SMART VILLAGE) DENGAN PENDEKATAN PENTA-HELIX UNTUK MEWUJUDKAN KEMANDIRIAN MASYARAKAT DESA DI ERA SOCIETY 5.0 - , Ririn Yulianti; Mira Andriani; Widya Yeshiana (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
The development of smart villages is critical to implement because it aims to improve the welfare and independence of village communities. However, in its implementation, many obstacles are faced, including the lack of involvement of stakeholders. Therefore, this study aims to reveal the synergy of penta-helix in developing smart villages in Handapherang Village, Ciamis Regency. We use a qualitative approach with a descriptive method. The informants in this study were all elements of the penta-helix involved in the development of smart villages in Handapherang Village, Ciamis Regency. The results of this study reveal that not all pillars of smart villages have been implemented, only four pillars, namely; smart government, smart environment, smart community, and smart economy. Some of the four pillars have not been implemented optimally. In addition, the synergy of penta-helix in the development of smart villages in Handapherang Village has not been maximized, there are still several actors who have not been maximally involved, including academic actors and business/private actors. In this study, we also reveal the inhibiting factors and supporting factors in the development of smart villages along with the penta helix synergy model with smart village pillars in realizing the independence of village communities.